Credit, asset prices and business cycles at the global level - Stéphane Dées (European Central Bank (ECB), 2016)
This paper assesses the role of financial variables in real economic fluctuations, in view of analysing the link between financial cycles and business cycles at the global level. A Global VAR modelling approach is used to first assess the contribution of credit and asset price variables to real economic activity in a number of countries and regions. The GVAR model is based on 38 countries estimated over 1987-2013. An analysis on a sample excluding the post-financial crisis period is also provided to check whether financial variables have gained importance in explaining business cycle fluctuations over the recent past. In a second step, financial shocks are identified through sign restrictions in order to illustrate how financial and business cycles could be related. Overall, the paper shows that the importance of credit and asset price variables in explaining real economic fluctuations is relatively large, but has not significantly increased since the global financial crisis. The international transmission of financial shocks on business cycle fluctuations also tends to be large and persistent.
Keywords: E32; E37; E44; E51; F47; 330; business cycle; financial cycle; GVAR model; international transmission of shocks